IMPROVING THE ELEVENTH GRADE STUDENTS' READING ACHIEVEMENT THROUGH LISTEN, READ AND DISCUSS (LRD) STRATEGY AT SMAN 1 GERUNG - M Asrul Hasby (JOETAL: Journal of Education, Teaching and Learning, 2025)
This study aims to find out Improving the eleventh grade students' reading achievement through listen, read and discuss  (LRD) strategy at SMAN 1 Gerung. This research is carried out using random sampling techniques, where all individuals in the population, either individually or together are given the same opportunity to be selected as sample members. This sampling and research is based on the considerations and recommendations of the English subject teacher, based on these considerations and recommendations, the class to be researched is class 11 F as many as 38 students as an experimental class. From the results of the study, the average pre-test score of students was 61.05 with a standard deviation of 10.46. Meanwhile, the post-test students obtained with an average score of 68.10 with a standard deviation of 9.18. Based on the calculations carried out with the T-test, the t-test was obtained which is 7.26 with a t-table of 1.68 for the actual level using 5% or 0.05. This shows that the t-test is greater than the t-table, which is 7.26>1.68, so Ho is rejected and Ha is accepted. From the results of the assessment, it can be concluded that there is a significant effect in increasing student reading achievement in using the LRD strategy.